O fortalecimento da resiliência de codependentes por meio de intervenção familiar sistêmica - Betina Stahlke Rabitzch, Anne; Roberto Krüger, Rolf (Vox Scripturae - Revista Teológica Internacional, 2012)
The present research articulates the theme of co-dependence under the systemic therapy’s eye, pointing to the possibility of strengthening the personal and familiar resilience. The co-dependent has a life profile turned to the “salvation” of others. Profile, which could have been molded by a dysfunctional familiar environment, in which, the child was the emotional support to one or more adults. Individuals that grow up in similar circumstances and turn into healthy adults are held as resilient. Resiliency which is not simply individual, but at least presents one healthy adult as emotional support in adverse circumstances. The treatment of co-dependence through the Systemic Familiar Therapy leads to the strengthening of personal and familiar resilience.
Keywords: Co-dependence; Systemic Familiar Therapy; Resilience